Generalized Boundary Closed Sets in Fuzzy Topological Spaces - Sanjivappa K Dembare (International Journal of Mathematics And its Applications, 2021)
In this paper, fuzzy boundary generalized closed set is introduced and studied. It is proved that every fuzzy closed set and fuzzy boundary closed set is fuzzy Boundary generalized closed set but the converses need not be true. Every fbg-closed set is fspg-closed, every fgs-closed and fpg-closed sets is fbg- closed, but the converses need not be true.